Estudo da flambagem local da mesa de perfis I com alma senoidal via análise não linear pelo MEF - Daniel Gordilho Souza (2006)
Flange local buckling of sinusoidal web I girders is investigated in this study. As a first step, pre-processors for ANSYS 9.0 are created, using the software parametric design language, for the non-linear numerical analysis of plane web and sinusoidal web I girders. A group of plane webs I girders is analyzed and the non-linear analysis parameters arecalibrated in order to get results consistent with the ones obtained by the Brazilian steel code, NBR8800 (under revision - sept/2006), design procedures. Using the pre-processors for sinusoidal web models and the non-linear analysis parameters calibrated in the plane web models, a parametric investigation is carried out, considering the application range of sinusoidal webs I girders. The numerical results obtained are compared to the ultimate capacity proposed by two different procedures as such: the NBR 8800 design process for plane web I girders and the sinusoidal web I girders design procedure used by the Austrianindustry Zeman, adapted to the NBR8800. It is verified that the Zeman design procedure, adapted do the NBR8800, is conservative. The NBR8800 design process, considering kc=0,763 as flange buckling coefficient, is consistent for the inelastic range and conservative for the elastic range. As a result of this study, a design procedure is proposed,based in the NBR 8800 design process, adapting the curve of the elastic range in order to attend the numerical results.